Penyuluhan Hukum Perlindungan Anak Pada Lembaga Kesejahteraan Sosial Anak (LKSA) Ittaqollah Kota Ambon - Astuti Nur Fadillah; Anna Maria Salamor; Patrick Corputty; Weldy M Risakotta (Faculty of Law Pattimura University, 2021)
Introduction: In the frequently modern era, many phenomena happen in civilization. Children as the nation's successors need to be protected from the negative impacts of rapid development, the flow of globalization in the field of communication and information, the advancement of science and technology. The negative impact of the development of this era creates problems involving children, both children as victims, perpetrators, and witnesses who are dealing with the law itself.Purposes of Devotion: The purpose of this article is to provide a brief overview of the law on child protection. The Unitary State of the Republic of Indonesia guarantees the welfare of every citizen, including the protection of children's rights which are human rights. Method of Devotion: This Community Service activity was carried out at the Ittaqollah Child Welfare Institution (LKSA) Ambon City. In this activity, several stages were carried out including observing the average age and needs of the Ittaqollah Children's Social Welfare Institution (LKSA) of Ambon City, and providing legal counseling on child protection. This service activity is carried out using the lecture and question and answer method which is packaged more attractively.Results of the Devotion: After carrying out this service activity, it was found that students at the Ittaqollah Child Welfare Institution (LKSA) had minimal knowledge of child protection laws. LKSA Ittaqolah students only know about the age limit of children, but they do not understand their rights as children who have been protected by the state. Moreover, they do not understand that children are very vulnerable to become victims of violations of their rights by adults. In addition, they also still do not understand that nowadays children are not only victims, but children can also commit crimes so that children can face the law.